Are Bismuth Shields Useful in Dentomaxillofacial Radiology Practice for the Protection of Eyes and Thyroid Glands from Ionizing Radiation? - GÜMRÜ TARÇIN, BİRSAY (KOWSAR PUBL, 2017)
Background: The eye lens and thyroid gland are sensitive to radiation and have a risk of being exposed to primary beams and scattered radiation during dental radiographic examinations. Objectives: The present study was aimed to evaluate the effectiveness of bismuth shielding in decreasing eye lens and thyroid radiation dose in periapical radiography (PR), orthopantomography (OPTG), and cone beam computed tomography (CBCT) examinations. There is no information in relevant literature regarding the use of bismuth shielding in dental radiology. Materials and Methods: Dose measurements for PR, OPTG and CBCT were conducted by placing thermoluminescent dosimeter chips on the eye and thyroid location in a standard head phantom. Each one of the scan techniques was performed without any bismuth shielding, and they were then repeated with bismuth shielding in place. The percent dose reduction from bismuth shielding was calculated by dividing the dose measured with bismuth shielding by the dose measured without bismuth shielding. Results: The eye dose was observed to decrease in bismuth shielding group in PR, however it was not statistically significant. The thyroid dose was found to be significantly decreased in PR (P < 0.05). In OPTG and CBCT scans, both the dose to the eye and the thyroid gland was observed to increase by using bismuth shielding. Among these, only the increase in the eye dose in CBCT was not statistically significant (P > 0.05). Conclusion: This study demonstrated higher thyroid and eye lens dose with the use of bismuth shielding in OPTG and CBCT scanning. However, due to the significantly decreased thyroid dose in PR, it may be recommended as an alternative to leaded shielding in periapical radiographic examinations.
Keywords: Periapical Radiography; Panoramic Radiography; Cone Beam Computed Tomography; Bismuth Shielding; Dose Reduction; DOSE REDUCTION; CT; BREAST